2012
DOI: 10.1159/000338793
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Cell Lines in the Study of Neuroendocrine Tumors

Abstract: Cell lines originating from neuroendocrine tumors (NETs) represent useful experimental models to assess the control of synthesis and release of different hormones and hormone-like peptides, to evaluate the mechanisms of action of these agents in target tissues at the cellular and subcellular levels, and to study cell proliferation and tumor development, as well as the effect of different drugs on these complex processes. To date, the understanding of NET biology (with regard to their mechanisms of hormone secr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 190 publications
(105 reference statements)
0
41
0
Order By: Relevance
“…TGF-β1 can act as either promoter, via EMT activation, or suppressor of tumor progression, depending on the degree of tumor malignancy [26]. In this context [3], we have reported its protective role in low-to-intermediate grade carcinoids, but the higher malignancy of NET cell lines is well documented [27, 28]. Therefore, here we used TGF-β1 as positive regulator of EMT and observed that this cytokine induced the transcriptional signature of EMT in all NET cell lines, with modifications similar to those caused by CXCL12 in CXCR4 high /CXCL12 low NET cells.…”
Section: Discussionmentioning
confidence: 99%
“…TGF-β1 can act as either promoter, via EMT activation, or suppressor of tumor progression, depending on the degree of tumor malignancy [26]. In this context [3], we have reported its protective role in low-to-intermediate grade carcinoids, but the higher malignancy of NET cell lines is well documented [27, 28]. Therefore, here we used TGF-β1 as positive regulator of EMT and observed that this cytokine induced the transcriptional signature of EMT in all NET cell lines, with modifications similar to those caused by CXCL12 in CXCR4 high /CXCL12 low NET cells.…”
Section: Discussionmentioning
confidence: 99%
“…In our study we used the well-known and highly proliferative BON1 cell line of human pancreatic carcinoid origin as a NET in vitro model [49]; whereas the important antiproliferative effect of CQ demonstrated here in BON1 cells may not be directly applicable to in vivo grade 1 or grade 2 (well-differentiated) NET models, they are probably suggestive for the possible efficacy of autophagy inhibition as a therapeutic target also in NET models with a lower proliferation rate. Indeed, the main limitation of our study is that all of the experiments were done on a cell line, and further experiments using primary tumors in mouse models are needed before human studies can be contemplated; however, these results are encouraging and suggest that lysosomal inhibitors, such as CQ, may become a new therapeutic approach for patients with metastatic NETs treated with or without mTORi.…”
Section: Discussionmentioning
confidence: 99%
“…GEPNET cell lines have been used to study selected inhibitors for their efficacy and mechanism of action (Grozinsky-Glasberg et al 2012). No comprehensive screening for effective inhibitors of GEPNETs has however been reported.…”
Section: Pannet and Sinet Cells Are Sensitive To Inhibitors Of Mek Anmentioning
confidence: 99%